P350 Endoscopic sedation in IBD patients: a propensity score-matched retrospective study. (30th January 2023) - Levartovsky, A; Cohen, T; Klang, E; Ben-Horin, S; Kopylov, U
Abstract: Background: Colonoscopy plays an essential role in the prevention of colorectal cancer screening and the management of inflammatory bowel disease (IBD). For patients with IBD, colonoscopy is advocated for detection of complications, guiding clinical decisions, and cancer surveillance. In most cases, sedation is a fundamental constituent of the procedure, reducing peri-procedural discomfort and improving examination quality. We aimed to compare the dosing of sedative medications and the duration of procedure for IBD patients compared to non-IBD controls in a large-volume endoscopic center. Methods: This was a propensity score–matched retrospective study that took place at a high-volume gastroenterology department between June 2020 and September 2021. Colonoscopy data of patients with established IBD including medications and duration of procedure was collected, compared to a 1:2 propensity-scored matched cohort of non-IBD patients. Patients with polyposis, past abdominal surgery, known or suspected malignancy, suspected IBD, incomplete colonoscopies and colonoscopies with inadequate preparation were excluded. The sedation protocol in our institution includes an induction of Midazolam 1-2 mg and Fentanyl of 0.025-0.05 mg administered five minutes prior to procedure. An initial dose of 10-30 mg Propofol is initiated as well, with subsequent increments of 10-20 mg every 1-2 minutes, depending on sedation depth. Results: During the study period, 14502 patients including 996 patients with IBD underwent colonoscopy and 4933 patients were excluded in accordance with the exclusion criteria. Propensity score matching was conducted using four characteristics - patient age, gender, American Society of anaesthesiologists score determined by the endoscopist, and endoscopists' experience. A total of 2289 patients were included in the final analysis (763 IBD patients, 1526 control patients). The groups were similar in administered Propofol sedation doses [IBD- median dose of 100 mg, interquartile ratio (IQR) 70-150 vs control, 100 mg, IQR 80-150, p=0.2). In addition, total procedure time (considered the time from procedure start and end as recorded by the endoscopy nurse) was significantly longer in the IBD group (23 median minutes, IQR 18-30 vs 20 median minutes, IQR 16-27, p<0.0001). There were no differences in terminal ileum intubation rates between the groups (51% in IBD vs 49.5% in control, p=0.5). Conclusion: In a retrospective analysis from a large-scale tertiary center cohort, colonoscopies of patients with IBD were significantly longer despite comparable terminal intubation rates; IBD patients did not require more intensive sedation than controls.